Method for producing a coated cutting tool and coated cutting tool

By depositing Ti1-xAlxN layer under specific conditions, the problem of difficult to maintain the cube crystal structure in the high aluminum content (Ti,Al) N layer is solved, and the high wear resistance and edge toughness of the coating are achieved, and the cutting tool is extended lifespan.

CN114040991BActive Publication Date: 2025-02-07SANDVIK COROMANT
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202080044852.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-06-19
Filing Date
2020-06-17
Publication Date
2025-02-07
Estimated Expiration
2040-06-17

AI Technical Summary

Technical Problem

The prior art is difficult to maintain the cubic crystal structure in the (Ti,Al) N layer with high alumina content, resulting in poor wear and edge integrity requirements of coatings in metal processing.

Method used

The Ti1-xAlxN layer is deposited by cathode arc evaporation with 0.70≤x≤0.98 using a DC bias voltage of -200 to -400V and an arc discharge current of 75A to 250A at a nitrogen vacuum chamber pressure of 7Pa to 15Pa, ensuring that There is a cubic crystal phase in the layer.

Benefits of technology

A single-phase cubic structure with (Ti,Al) N layer under high aluminum content is realized, which improves the wear resistance of the backplane, crescent abrasion resistance and edge toughness of the coating, and extends the use of cutting tools. life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114040991B_ABST
    Figure CN114040991B_ABST
Patent Text Reader

Abstract

The present invention relates to a method for manufacturing a coated cutting tool for metal processing, the coated cutting tool comprising a substrate (100) and a coating (101), the coating comprising at least one (Ti, Al) N layer containing a cubic phase, the method comprising depositing Ti 1‑ x Al x N layers, where 0.70≤x≤0.98, Ti 1‑x Al x N contains a cubic phase, the Ti 1‑x Al x The N layer is deposited by cathodic arc evaporation using a DC bias voltage of ‑200 V to ‑400 V and using an arc discharge current of 75 A to 250 A at a vacuum chamber pressure of 7 Pa to 15 Pa of N2 gas. The present invention also relates to a coated cutting tool for metal processing having a coating comprising at least Ti 1‑y Al y N and Ti 1‑z Al z In the (Ti,Al)N multilayers of alternating sublayers of N, where 0.35≤y≤0.65 and 0.80≤z≤0.98, only the cubic phase exists.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention relates to a method for manufacturing a coated cutting tool having a (Ti,Al)N layer containing a cubic crystal structure and having a high aluminum content. The present invention also relates to a coated cutting tool. Background Art

[0002] (Ti,Al)N coatings made by physical vapor deposition (PVD) are commonly used in the field of cutting tools for metalworking.

[0003] The crystal structure of (Ti,Al)N in PVD coatings can be a cubic (NaCl(=B1)) structure or a hexagonal (wurtzite) structure. In prior art studies, generally, a lower Al content in (Ti,Al)N (e.g., < 60% of Al+Ti) provides a cubic structure, while a high Al content (e.g., > 70%) provides a hexagonal structure. Specific limits for the Al content levels for providing a single-phase cubic structure or a mixed structure containing a cubic structure and a hexagonal structure have been reported and vary to some extent depending on, for example, deposition conditions.

[0004] It is known that single-phase cubic (Ti,Al)N layers have good properties in terms of hardness and elastic modulus. These properties are beneficial for the coatings of cutting tools.

[0005] For example, Tanaka et al., "Properties of (Ti 1-x Al x )N coatings for cutting tools prepared by the cathodic arc ion plating method", Journal of Vacuum Science & Technology A 10, 1749 (1992) reported that (Ti 1-x Al x )N films are single-phase up to x = 0.6 and have a cubic B1 structure, while a further increase in the aluminum content (x = 0.85) results in a wurtzite structure. In addition, Kimura et al., "Effects of Al content on hardness, lattice parameter and microstructure of (Ti 1-x Al x )N films", 1-x Al x )N films", 1-x Al x)N films)", Surface and Coatings Technology 120–121 (1999) 438-441 reported that (Ti) 1-x Al x )N film, in which the NaCl structure (x≤0.6) is transformed into the wurtzite structure (x≥0.7).

[0006] WO2019 / 048507A1 discloses a method for manufacturing a (Ti,Al)N film with a high aluminum content by using a high power impulse magnetron sputtering (HIPIMS) technique, wherein the film exhibits a crystalline cubic phase.

[0007] When depositing (Ti,Al)N films by cathodic arc evaporation, a bias voltage is applied and the reaction chamber has a specific level of nitrogen pressure. Typical bias voltage levels are -30 V to -150 V. The higher the voltage, the higher the energy in the plasma.

[0008] A typical nitrogen pressure level is 2Pa to 6Pa. The higher the nitrogen pressure, the higher the number of nitrogen molecules per unit volume. Nitrogen molecules suppress the energy of ions and particles in the plasma. Therefore, the higher the nitrogen pressure, the more obvious this effect is. Thus, when using a high level of bias voltage, the nitrogen pressure has traditionally been kept low so as not to conflict with the desired effect of using a high bias voltage.

[0009] It is an object of the present invention to provide a method for producing a (Ti,Al)N layer having a high aluminum content and still containing a cubic phase.

[0010] There is a continuing need for coated cutting tools where the coating has good resistance to various types of wear, such as flank wear and crater wear, in order to provide long tool life in metalworking applications. In addition, certain applications have high demands on the edge line integrity of the cutting tool, i.e., high edge line toughness is required.

[0011] Therefore, another object of the present invention is to provide a coated cutting tool having good flank wear resistance and / or good crater wear resistance and / or good edge line toughness. Summary of the invention

[0012] A method for producing a coated cutting tool for metal machining has now been provided, the coated cutting tool comprising a substrate and a coating, the coating comprising at least one (Ti,Al)N layer comprising a cubic phase and having a high aluminum content.

[0013] The presence of a cubic phase in the (Ti,Al)N layer is defined herein as the presence of one or more cubic peaks in the θ-2θ XRD analysis.

[0014] The method comprises depositing Ti 1-x Al x N layers, where 0.70≤x≤0.98, Ti 1-x Al x N contains a cubic phase, the Ti 1-x Al x The N layer is deposited by cathodic arc evaporation using a DC bias voltage of -200 to -400 V, preferably -250 V to -350 V and using an arc discharge current of 75 A to 250 A, preferably 100 A to 200 A under a vacuum chamber pressure of 7 Pa to 15 Pa, preferably 8 Pa to 12 Pa of N2 gas.

[0015] The (Ti,Al)N layer prepared according to the present method can be deposited as a single layer. 1-x Al x The thickness of the N layer is suitably 0.2 μm to 10 μm, preferably 0.5 μm to 5 μm.

[0016] In one embodiment, the method provides a monolayer (Ti,Al)N comprising a cubic crystal structure with an aluminum content (Al+Al in Ti) of at least up to 80 atomic % or even up to 85 atomic %. The cubic (Ti,Al)N phase may be present to the extent that it is a single phase in the (Ti,Al)N layer, or the cubic (Ti,Al)N phase may be present together with a hexagonal (Ti,Al)N phase. Thus, in one embodiment of the method, the Ti 1-x Al x The N layer is a single layer having a cubic crystal structure, wherein 0.70≤x≤0.85. 1-x Al x The N layer is a single layer including a cubic crystal structure, wherein 0.70≤x≤0.80.

[0017] In another embodiment of the method, the Ti 1-x Al x The N layer is a single layer having a cubic crystal structure, wherein 0.75≤x≤0.85. In another embodiment of the method, the Ti 1-x Al x The N layer is a single layer having a cubic crystal structure, wherein 0.75≤x≤0.80.

[0018] For aluminum contents (Al+Al in Ti) above 75 atomic % or above 80 atomic %, when the (Ti,Al)N layer is a single layer, the cubic (Ti,Al)N phase is suitably present together with the hexagonal (Ti,Al)N phase. For aluminum contents equal to or below 75 atomic %, preferably below or equal to 80 atomic %, the cubic (Ti,Al)N phase is suitably the only (Ti,Al)N phase present.

[0019] The (Ti,Al)N layer produced according to the method can also be used as part of a multilayer coating in which Ti 1-x Al x The N sublayer is present in a repeating manner with at least one further (Ti, Al) N sublayer. Such an embodiment of the (Ti, Al) N multilayer has alternating layers of at least two different sublayers (A, B, C ...), which are repeated in a manner such as A / B / C ... / A / B / C ... / ... or A / B / A / B / ...., wherein the (Ti, Al) N sublayers A, B, C ... have different Ti / Al ratios from one another.

[0020] The average thickness of each (Ti,Al)N sub-layer is suitably from 1 to 20 nm, preferably from 1 to 10 nm, most preferably from 1.5 to 5 nm.

[0021] For multilayer (Ti,Al)N, a single-phase cubic structure of (Ti,Al)N sublayers up to a higher Al content than that of single-layer (Ti,Al)N can be obtained.

[0022] In one embodiment, the (Ti,Al)N multilayer is at least Ti 1-y Al y N and Ti 1-z Al z For multilayers of alternating sublayers of N, where 0.35≤y≤0.65 and 0.80≤z≤0.98, only the cubic phase exists.

[0023] In one embodiment, 0.35≤y≤0.65 and 0.85≤z≤0.96.

[0024] In one embodiment, 0.40≤y≤0.60 and 0.80≤z≤0.98.

[0025] In one embodiment, 0.40≤y≤0.60 and 0.85≤z≤0.96.

[0026] The substrate of the coated cutting tool may be selected from cemented carbide, cermet, ceramic, cubic boron nitride and high speed steel. Preferably, the substrate of the coated cutting tool is cemented carbide.

[0027] There is now also provided a coated cutting tool for metal machining comprising a substrate and a coating comprising a multilayer of alternating sublayers of cubic (Ti,Al)N.

[0028] The coated cutting tool comprises at least Ti 1-y Al y N and Ti 1-z Al z A multilayer of alternating sublayers of N, wherein 0.35≤y≤0.65 and 0.80≤z≤0.98, only a cubic phase is present (as detected by XRD θ-2θ analysis), and the average thickness of a single (Ti,Al)N sublayer is 1 to 20 nm. The term "only a cubic phase is present" means that no hexagonal (Ti,Al)N peak is seen in the θ-2θ XRD analysis, and only one or more cubic (Ti,Al)N peaks are present.

[0029] The sublayer Ti 1-y Al y The thickness of N has a great influence on the Ti sublayer 1-z Al z The ratio of the thickness of N is suitably ≥0.5 and <3, preferably 0.75 to 2.

[0030] In one embodiment, the (Ti,Al)N multilayer comprises at least three alternating sublayers of different sublayers (A, B, C...), which are repeated in the manner of ...A / B / C... / A / B / C... / ..., and the composition of any sublayer A, B, C... is Ti 1-v Al v N, 0.35≤v≤0.98, the two sublayers are Ti 1-w Al w N and Ti 1-r Al r N, where 0.35≤w≤0.65 and 0.8≤r≤0.98.

[0031] In one embodiment, the (Ti,Al)N multilayer is Ti 1-y Al y N and Ti 1-z Al z A multilayer of alternating sublayers of N, wherein 0.35≤y≤0.65 and 0.80≤z≤0.98.

[0032] In one embodiment, 0.35≤y≤0.65 and 0.85≤z≤0.96.

[0033] In one embodiment, 0.40≤y≤0.60 and 0.80≤z≤0.98.

[0034] In one embodiment, 0.40≤y≤0.60 and 0.85≤z≤0.96.

[0035] The average thickness of the individual sublayers is suitably from 1 to 10 nm, preferably from 1.5 to 5 nm.

[0036] In one embodiment, the (Ti,Al)N is a non-periodic multilayer. In this type of multilayer, there may be some differences in thickness of the sublayers, even for sublayers of the same composition. This type of multilayer is typically produced by a deposition process using a triple rotation of rotating cutting tool blanks in a PVD chamber.

[0037] In one embodiment, the (Ti,Al)N is a periodic multilayer. In this type of multilayer, each constituent sublayer has approximately the same thickness.

[0038] The total thickness of the (Ti,Al)N multilayer is 0.5 μm to 10 μm, or 1 μm to 8 μm, or 2 μm to 6 μm.

[0039] The (Ti,Al)N multilayer is suitably a cathodic arc evaporation deposited layer.

[0040] In one embodiment, the coating comprises one or more additional metal nitride layers below the (Ti, Al) N multilayer. The metal nitride is suitably a nitride of one or more metals belonging to Groups 4 to 6 of the IUPAC Periodic Table, optionally formed together with Al and / or Si. Examples of such metal nitrides are TiN and (Ti, Al) N. The total thickness of these one or more metal nitride layers may be from about 0.1 μm to about 2 μm, or from about 0.2 μm to about 1 μm.

[0041] The substrate of the coated cutting tool may be selected from cemented carbide, cermet, ceramic, cubic boron nitride and high speed steel. Preferably, the substrate of the coated cutting tool is cemented carbide.

[0042] The coated cutting tool may be a cutting tool insert, a drill or a solid end mill for metal machining. The cutting tool insert is suitably a milling, drilling or turning insert.

[0043] The (Ti,Al)N layer herein may contain a small amount of additional metal Me as part of the nitride, such as Cr, Zr and Si, in an atomic percentage of up to 3 atomic % (Me+Al+Me in Ti), or even up to 5 atomic %, without substantially changing the properties of the coating. If Me is present, then in the (Ti,Al)N formula used herein, Me will be counted as Ti. Thus, the Ti content in (Ti,Al)N is then actually the Ti+Me content. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 A schematic diagram of a substrate (100) having a coating (101) according to the present invention is shown.

[0045] Figure 2 Shown are X-ray diffraction patterns of samples deposited with (Ti,Al)N layers at different bias voltages and / or pressures.

[0046] Figure 3 X-ray diffraction patterns of (Ti,Al)N monolayers with different Al contents deposited by conventional methods are shown.

[0047] Figure 4 X-ray diffraction patterns of (Ti,Al)N monolayers with different Al contents deposited by the method of the present invention are shown.

[0048] Figure 5 X-ray diffraction patterns of (Ti,Al)N multilayers with different Al contents deposited by conventional methods are shown.

[0049] Figure 6 X-ray diffraction patterns of (Ti,Al)N multilayers with different Al contents deposited by the method of the present invention are shown.

[0050] Figure 7 Shows Ti 0.10 Al 0.90 N / Ti 0.50 Al 0.50 N and Ti 0.05 Al 0.95 N / Ti 0.50 Al 0.50 X-ray diffraction pattern of N multilayer. Example

[0051] Embodiment 1:

[0052] Different Ti 0.20 Al 0.80 The N coating was deposited by cathodic arc evaporation on a sintered cemented carbide cutting tool insert blank SNMA120808-KR. The composition of the cemented carbide was 10 wt.% Co, the remainder WC. Samples 1-4 were deposited in triple rotation using a rotating table with a "tree" of pins on which the blanks were mounted. The reaction chamber contained four flanges for the targets. The Ti 0.20 Al 0.80 The targets are mounted on two opposite flanges, and the other two flanges are empty. Evacuate the chamber to a vacuum (less than 10 -2Pa) and heated to about 450 ° C by a heater inside the chamber. The blank was etched in Ar plasma for 60 minutes. The chamber pressure (reaction pressure) was set to 4 Pa ​​or to 10 Pa of N2 gas and the expected DC bias voltages of samples 1-4 were -50 V, -225 V, -300 V and -375 V, respectively, see Table 1. The cathode was operated in arc discharge mode with a current of 150 A (each). A 3 μm layer was deposited.

[0053] Table 1.

[0054]

[0055] X-ray diffraction (XRD) analysis of the flank face of the coated inserts was performed using a PANalytical CubiX3 diffractometer equipped with a PIXcel detector. The coated cutting tool inserts were mounted in a sample holder, ensuring that the flank face of the sample was parallel to the reference surface of the sample holder and also that the flank face was at the appropriate height. α Radiation was used for the measurement with a voltage of 45 kV and a current of 40 mA. An anti-scatter slit of 1 / 2 degree and a divergence slit of 1 / 4 degree were used. The diffraction intensity from the coated cutting tool was measured around the 2θ angle where the relevant peak appeared.

[0056] Figure 2 Diffraction patterns of samples 1-4 are shown.

[0057] It was concluded that essentially no hexagonal signals were seen for samples made using 10 Pa nitrogen pressure and substrate bias voltages of -300 V and -225 V. Sample 1, using conventional parameters, showed no visible cubic signals (e.g., (2 0 0) reflections) in the diffraction pattern. Sample 4 showed cubic (2 0 0) reflections, but also showed significant hexagonal (1 1 -2 0) reflections.

[0058] Embodiment 2:

[0059] Ti 0.10-0.40 Al 0.60-0.90 The different coatings of N were obtained by using three different targets Ti 0.40 Al 0.60 、Ti 0.25 Al 0.75 and Ti 0.10 Al 0.90 These targets are located in groups of three at different heights on all four flanges in the reaction chamber. Thus, the composition of the coating differs in a progressive manner depending on the position of the blank in the chamber.

[0060] The first set of samples was made by depositing a (Ti,Al)N layer on a cutting tool insert cemented carbide blank of the same geometry SNMA120808-KR as in Example 1, using a deposition procedure as described in Example 1, using a DC bias voltage of -50 V and a nitrogen pressure of 4 Pa. The blank was first etched in Ar plasma for 60 minutes. The thickness of the coating was about 3 μm.

[0061] The second set of samples was made by depositing a (Ti,Al)N layer on a cutting tool insert cemented carbide blank using the deposition procedure as described in Example 1, using a DC bias voltage of -300 V and a nitrogen pressure of 10 Pa. The blank was first etched in Ar plasma for 60 minutes. The thickness of the coating was about 3 μm.

[0062] Samples from 14 different levels in the reaction chamber were analyzed by XRD. The Al content in the coating (relative to Ti+Al) was also analyzed by EDS. See Table 2 for samples 5-18 deposited at -50V DC bias and 4Pa nitrogen pressure, and Table 3 for samples 19-32 deposited at -300V DC bias and 10Pa nitrogen pressure. For the second set of samples, not all samples were analyzed (see Table 3), but the gradual increase in Al content of the different samples is obvious.

[0063] Table 2.

[0064] <![CDATA[Sample Ti 1-x Al x N]]> x 5 <h2 style=";text-align:left;direction:ltr"><![CDATA[Ti <h2 style=";text-align:left;direction:ltr"> 1-x <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> N]]><h2 style=";text-align:left;direction:ltr"> 0.61 6 <h2 style=";text-align:left;direction:ltr"><![CDATA[Ti <h2 style=";text-align:left;direction:ltr"> 1-x <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> N]]><h2 style=";text-align:left;direction:ltr"> 0.63 7 <h2 style=";text-align:left;direction:ltr"><![CDATA[Ti <h2 style=";text-align:left;direction:ltr"> 1-x <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> N]]><h2 style=";text-align:left;direction:ltr"> 0.64 8 <h2 style=";text-align:left;direction:ltr"><![CDATA[Ti <h2 style=";text-align:left;direction:ltr"> 1-x <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> N]]><h2 style=";text-align:left;direction:ltr"> 0.66 9 <h2 style=";text-align:left;direction:ltr"><![CDATA[Ti <h2 style=";text-align:left;direction:ltr"> 1-x <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> N]]><h2 style=";text-align:left;direction:ltr"> 0.67 10 <h2 style=";text-align:left;direction:ltr"><![CDATA[Ti <h2 style=";text-align:left;direction:ltr"> 1-x <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> N]]><h2 style=";text-align:left;direction:ltr"> 0.69 11 <h2 style=";text-align:left;direction:ltr"><![CDATA[Ti <h2 style=";text-align:left;direction:ltr"> 1-x <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> N]]><h2 style=";text-align:left;direction:ltr"> 0.70 12 <h2 style=";text-align:left;direction:ltr"><![CDATA[Ti <h2 style=";text-align:left;direction:ltr"> 1-x <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> N]]><h2 style=";text-align:left;direction:ltr"> 0.76 13 <h2 style=";text-align:left;direction:ltr"><![CDATA[Ti <h2 style=";text-align:left;direction:ltr"> 1-x <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> N]]><h2 style=";text-align:left;direction:ltr"> 0.78 14 <h2 style=";text-align:left;direction:ltr"><![CDATA[Ti <h2 style=";text-align:left;direction:ltr"> 1-x <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> N]]><h2 style=";text-align:left;direction:ltr"> 0.83 15 <h2 style=";text-align:left;direction:ltr"><![CDATA[Ti <h2 style=";text-align:left;direction:ltr"> 1-x <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> N]]><h2 style=";text-align:left;direction:ltr"> 0.82 16 <h2 style=";text-align:left;direction:ltr"><![CDATA[Ti <h2 style=";text-align:left;direction:ltr"> 1-x <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> N]]><h2 style=";text-align:left;direction:ltr"> 0.84 17 <h2 style=";text-align:left;direction:ltr"><![CDATA[Ti <h2 style=";text-align:left;direction:ltr"> 1-x <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> N]]><h2 style=";text-align:left;direction:ltr"> 0.86 18 <h2 style=";text-align:left;direction:ltr"><![CDATA[Ti <h2 style=";text-align:left;direction:ltr"> 1-x <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> N]]><h2 style=";text-align:left;direction:ltr"> 0.85

[0065] Table 3.

[0066] sample x 19 <h2 style=";text-align:left;direction:ltr"><![CDATA[Ti <h2 style=";text-align:left;direction:ltr"> 1-x <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> N]]><h2 style=";text-align:left;direction:ltr"> 0.60 20 <h2 style=";text-align:left;direction:ltr"><![CDATA[Ti <h2 style=";text-align:left;direction:ltr"> 1-x <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> N]]><h2 style=";text-align:left;direction:ltr"> -* 21 <h2 style=";text-align:left;direction:ltr"><![CDATA[Ti <h2 style=";text-align:left;direction:ltr"> 1-x <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> N]]><h2 style=";text-align:left;direction:ltr"> 0.63 22 <h2 style=";text-align:left;direction:ltr"><![CDATA[Ti <h2 style=";text-align:left;direction:ltr"> 1-x <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> N]]><h2 style=";text-align:left;direction:ltr"> -* 23 <h2 style=";text-align:left;direction:ltr"><![CDATA[Ti <h2 style=";text-align:left;direction:ltr"> 1-x <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> N]]><h2 style=";text-align:left;direction:ltr"> 0.67 24 <h2 style=";text-align:left;direction:ltr"><![CDATA[Ti <h2 style=";text-align:left;direction:ltr"> 1-x <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> N]]><h2 style=";text-align:left;direction:ltr"> -* 25 <h2 style=";text-align:left;direction:ltr"><![CDATA[Ti <h2 style=";text-align:left;direction:ltr"> 1-x <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> N]]><h2 style=";text-align:left;direction:ltr"> 0.72 26 <h2 style=";text-align:left;direction:ltr"><![CDATA[Ti <h2 style=";text-align:left;direction:ltr"> 1-x <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> N]]><h2 style=";text-align:left;direction:ltr"> 0.74 27 <h2 style=";text-align:left;direction:ltr"><![CDATA[Ti <h2 style=";text-align:left;direction:ltr"> 1-x <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> N]]><h2 style=";text-align:left;direction:ltr"> -* 28 <h2 style=";text-align:left;direction:ltr"><![CDATA[Ti <h2 style=";text-align:left;direction:ltr"> 1-x <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> N]]><h2 style=";text-align:left;direction:ltr"> 0.78 29 <h2 style=";text-align:left;direction:ltr"><![CDATA[Ti <h2 style=";text-align:left;direction:ltr"> 1-x <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> N]]><h2 style=";text-align:left;direction:ltr"> -* 30 <h2 style=";text-align:left;direction:ltr"><![CDATA[Ti <h2 style=";text-align:left;direction:ltr"> 1-x <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> N]]><h2 style=";text-align:left;direction:ltr"> 0.81 31 <h2 style=";text-align:left;direction:ltr"><![CDATA[Ti <h2 style=";text-align:left;direction:ltr"> 1-x <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> N]]><h2 style=";text-align:left;direction:ltr"> -* 32 <h2 style=";text-align:left;direction:ltr"><![CDATA[Ti <h2 style=";text-align:left;direction:ltr"> 1-x <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> N]]><h2 style=";text-align:left;direction:ltr"> 0.87

[0067] *Not analyzed

[0068] Figure 3 X-ray diffraction patterns of (Ti,Al)N monolayers of samples 5-18 with different Al contents deposited using conventional methods are shown.

[0069] Figure 4 X-ray diffraction patterns of (Ti,Al)N monolayers of samples 19-32 with different Al contents deposited by the method of the present invention are shown.

[0070] from Figure 3(Coating deposited using conventional methods) It can be seen that cubic (2 0 0) reflections are noticed until the Al content (relative to Ti+Al) is as high as about 66 atomic %, and clearly visible hexagonal reflections (0 0 0 2) begin to be seen at about 63 atomic % Al content, and visible hexagonal reflections (1 1 -20) and (1 0 -1 0) begin to be seen at about 76 atomic % Al content.

[0071] from Figure 4 (Using the coating deposited according to the method of the invention) it can be seen that the cubic (2 0 0) reflection is noticed up to an Al content (relative to Ti+Al) of about 80 atomic %, and only for Al contents starting at about 81 atomic % are clearly visible hexagonal reflections (1 1 -2 0) and (1 0 -1 0) seen.

[0072] It is concluded that the method according to the invention provides a cubic structure up to a much higher Al content than conventional methods.

[0073] Embodiment 3:

[0074] By using three different targets Ti 0.40 Al 0.60 、Ti 0.25 Al 0.75 and Ti 0.10 Al 0.90 Made of different Ti 0.10- 0.40 Al 0.60-0.90 N / Ti 0.50 Al 0.50 N multilayer coating, the targets are located as a group of three targets at different heights on two opposite flanges in the reaction chamber, and Ti 0.50 Al 0.50 The targets are located on the two remaining opposing flanges. Thus, the composition of a sublayer in the multilayer coating differs in a progressive manner depending on the position of the blank in the chamber.

[0075] The first set of samples was made by depositing multiple layers on a cutting tool insert cemented carbide blank of the same geometry SNMA120808-KR as in Example 1, using a deposition procedure as described in Example 1, using a DC bias voltage of -50 V and a nitrogen pressure of 4 Pa. The blank was etched in Ar plasma for 60 minutes. First, about 0.3 μm Ti was deposited on the cemented carbide substrate using a DC bias voltage of -50 V and a nitrogen pressure of 4 Pa. 0.50 Al 0.50 N. The thickness of the coating was about 3 μm. A non-periodic multilayer was provided. The average sublayer thickness of the two different types of sublayers was each about 2 nm.

[0076] The second set of samples was made by depositing multiple layers on a cutting tool insert cemented carbide blank using the deposition procedure described in Example 1, using a DC bias voltage of -300 V and a nitrogen pressure of 10 Pa. The blank was etched in an Ar plasma for 60 minutes. First, about 0.3 μm Ti was deposited on the cemented carbide substrate using a DC bias voltage of -50 V and a nitrogen pressure of 4 Pa. 0.50 Al 0.50 N. The thickness of the coating was about 3 μm. A non-periodic multilayer was provided. The average sublayer thickness of the two different types of sublayers was each about 1.5 nm.

[0077] Samples from 17 different levels in the reaction chamber were analyzed by XRD. The Al content in the coating (relative to Ti+Al) was also analyzed by EDS. From each EDS result, except for Ti 0.50 Al 0.50 Sublayer Ti other than N 1-x Al x The N sublayer composition is based on the target composition and assuming that Ti 1-x Al x N and Ti 0.50 Al 0.50 The thickness of N sublayers is estimated to be equal.

[0078] See Table 4, which shows samples 33-49 deposited at a DC bias voltage of -50 V and a nitrogen pressure of 4 Pa, and Table 5 shows samples 50-66 deposited at a DC bias voltage of -300 V and a nitrogen pressure of 10 Pa. As can be seen from the table, not all samples were analyzed, but the gradual increase in Al content of different samples is obvious.

[0079] Table 4.

[0080]

[0081] *Not analyzed

[0082] Table 5.

[0083]

[0084] *Not analyzed

[0085] Figure 5 X-ray diffraction patterns of samples 33-49 of the entire (Ti,Al)N multilayer are shown, where all sublayers were deposited using conventional methods.

[0086] Figure 6X-ray diffraction patterns of samples 50-66 of the entire (Ti,Al)N multilayer are shown, wherein all sublayers are deposited using the method of the present invention.

[0087] Depend on Figure 5 (Multilayer coating deposited using conventional methods) It can be seen that starting from an Al content (relative to Ti+Al) of about 77 atomic % in one sublayer, clearly visible hexagonal reflections (0 0 0 2) can be seen.

[0088] according to Figure 6 Even at an Al content of about 87 atom % (relative to Ti+Al) in one sublayer (using a multilayer coating deposited by the method according to the invention), no hexagonal reflections are visible at all.

[0089] It is concluded that the method according to the invention provides a single-phase cubic structure up to a much higher Al content than conventional methods. In addition, a single-phase cubic structure is provided in a multilayer according to the invention, which has an Al content of at least 87 atom % (relative to Ti+Al) in one sublayer.

[0090] Embodiment 4:

[0091] By using Ti 0.10 Al 0.90 Target (or Ti 0.05 Al 0.95 target) and the Ti located on the other two opposite flanges 0.50 Al 0.50 Target, made of Ti 0.10 Al 0.90 N / Ti 0.50 Al 0.50 N and Ti 0.05 Al 0.95 N / Ti 0.50 Al 0.50 Other samples of multilayer coatings of N.

[0092] A set of samples ("Samples 67 and 68") were prepared by depositing Ti on carbide blanks of cutting tool inserts of turning insert geometry CNMG120804-MM (Samples 67a and 68a) and milling insert geometry R390-11T308M-PM (Samples 67b and 68b), respectively. 0.10 Al 0.90 N / Ti 0.50 Al 0.50 N and Ti 0.05 Al 0.95 N / Ti 0.50 Al 0.50The cemented carbide has the same composition as in Example 1 and is deposited using the deposition procedure described in Example 1 using a DC bias voltage of -50 V and a nitrogen pressure of 4 Pa. The blank is etched in Ar plasma for 60 minutes. First, about 0.3 μm Ti is deposited on the cemented carbide substrate using a DC bias voltage of -50 V and a nitrogen pressure of 4 Pa. 0.50 Al 0.50 N. The thickness of the coating was about 3 μm. A non-periodic multilayer was provided. The average sublayer thickness of the two different types of sublayers in each sample was about 2 nm each.

[0093] Then, Ti was deposited on the cutting tool insert carbide blanks of the turning insert geometry CNMG120804-MM (samples 69a and 70a) and the milling insert geometry R390-11T308M-PM (samples 69b and 70b), respectively. 0.10 Al 0.90 N / Ti 0.50 Al 0.50 N and Ti 0.05 Al 0.95 N / Ti 0.50 Al 0.50 A set of samples ("Samples 69 and 70") were made by multilayers of alternating sublayers of N. The cemented carbide had the same composition as in Example 1 and was deposited using the deposition procedure described in Example 1 using a DC bias voltage of -300 V and a nitrogen pressure of 10 Pa. The blanks were etched in Ar plasma for 60 minutes. First, about 0.3 μm Ti was deposited on the cemented carbide substrate using a DC bias voltage of -50 V and a nitrogen pressure of 4 Pa. 0.50 Al 0.50 N. The thickness of the coating was about 3 μm. A non-periodic multilayer was provided. The average sublayer thickness of the two different types of sublayers in the corresponding samples was each about 1.5 nm.

[0094] The actual composition of the multilayer was not analyzed, but it is estimated that the composition of the multilayer is very similar to the target composition, i.e., Ti 0.10 Al 0.90 N / Ti 0.50 Al 0.50 N and Ti 0.05 Al 0.95 N / Ti 0.50 Al 0.50 N. There may be a difference of a few percentage points.

[0095] Figure 7 The whole Ti of samples 67a and 68a made by conventional methods and samples 69a and 70a made by the method according to the present invention is shown. 0.10 Al0.90 N / Ti 0.50 Al 0.50 N and Ti 0.05 Al 0.95 N / Ti 0.50 Al 0.50 X-ray diffraction pattern of N multilayer.

[0096] from Figure 7 It can be concluded that the sample with the multilayer coating deposited using the conventional method has clearly visible hexagonal (0 0 0 2) reflections in the diffraction pattern. The sample with the multilayer coating deposited using the method according to the invention shows no hexagonal reflections.

[0097] It is concluded that the method according to the invention provides a single-phase cubic structure up to a much higher Al content than conventional methods. In addition, a single-phase cubic structure is provided in a multilayer according to the invention, the multilayer having an Al content of at least about 95 atomic % (relative to Ti+Al) in one sublayer.

[0098] Explanation of terms used in Examples 5-7:

[0099] The following expressions / terms are commonly used in metal cutting but are explained in the table below:

[0100] V c (m / min): Cutting speed (m / min)

[0101] f n (mm / rev): Feed rate per revolution (in turning)

[0102] a p (mm): Axial cutting depth (mm)

[0103] Embodiment 5:

[0104] Flank wear test:

[0105] Longitudinal turning

[0106] Workpiece material: Uddeholm Sverker 21 (tool steel), hardness ~210HB, D=180, L=700mm,

[0107] V c =125m / min

[0108] f n =0.072mm / revolution

[0109] a p =2mm

[0110] No cutting fluid

[0111] The cut-off criterion for tool life is flank wear VB of 0.15 mm.

[0112] The coating of sample 67a containing a hexagonal phase prepared by a conventional method, namely Ti 0.10 Al 0.90 N / Ti 0.50 Al 0.50 The coating of sample 69a manufactured by the method according to the present invention and having a single-phase cubic structure, namely Ti 0.10 Al 0.90 N / Ti 0.50 Al 0.50 N for comparison.

[0113] Embodiment 6:

[0114] Crater wear test:

[0115] Longitudinal turning

[0116] Workpiece material: Ovako 825B, ball bearing steel. After hot rolling and annealing, hardness ~200HB, D=160, L=700mm,

[0117] V c =160m / min

[0118] f n =0.3mm / turn

[0119] a p =2mm

[0120] With cutting fluid

[0121] The tool life ends when the crater area is 0.8mm 2 .

[0122] The coating of sample 67a containing a hexagonal phase prepared by a conventional method, namely Ti 0.10 Al 0.90 N / Ti 0.50 Al 0.50 The coating of sample 69a manufactured by the method according to the present invention and having a single-phase cubic structure, namely Ti 0.10 Al 0.90 N / Ti 0.50 Al 0.50 N for comparison.

[0123] Embodiment 7:

[0124] Thermal crack resistance ("comb crack" resistance) test :

[0125] Milling

[0126] Workpiece material: Toolox33, PK158 600x200x100mm, P2.5.Z.HT

[0127] z=1

[0128] V c =250m / min

[0129] f z =0.20mm

[0130] a e =12.5mm

[0131] a p =3.0

[0132] With cutting fluid

[0133] The cut-off criteria are met when the crack results in edge chipping >0.30 mm. Tool life is expressed as the number of cuts to meet these criteria.

[0134] The coating of sample 67b containing a hexagonal phase prepared by a conventional method, namely Ti 0.10 Al 0.90 N / Ti 0.50 Al 0.50 The coating of sample 69b manufactured by the method according to the present invention and having a single-phase cubic structure, namely Ti 0.10 Al 0.90 N / Ti 0.50 Al 0.50 N for comparison.

[0135] The test results in Examples 5-7 are shown in Table 6.

[0136] Table 6.

[0137]

[0138] It was concluded that the samples according to the invention have better resistance to flank wear, crater wear and comb cracks than the comparative samples.

Claims

1. A method for manufacturing a coated cutting tool for metal processing, the coated cutting tool comprising a substrate and a coating, the coating comprising at least one (Ti,Al)N layer containing a cubic phase, the method comprising depositing Ti 1-x Al x N layer, Ti 1-x Al x N contains a cubic phase, the Ti 1-x Al x The N layer is deposited by cathodic arc evaporation using a DC bias voltage of -200V to -350V and an arc discharge current of 100A to 200A in a vacuum chamber pressure of 10Pa to 15Pa of N2 gas, The Ti 1-x Al x The N layer is a single layer having a cubic crystal structure and a thickness of 0.2 μm to 10 μm, wherein 0.70≤x≤0.

80.

2. A method for manufacturing a coated cutting tool for metal processing, the coated cutting tool comprising a substrate and a coating, the coating comprising at least one (Ti,Al)N layer containing a cubic phase, the method comprising depositing Ti 1-x Al x N layers, where 0.70≤x≤0.98, Ti 1-x Al x N contains a cubic phase, the Ti 1-x Al x The N layer is deposited by cathodic arc evaporation using a DC bias voltage of -200V to -350V and an arc discharge current of 100A to 200A in a vacuum chamber pressure of 10Pa to 15Pa of N2 gas, The Ti 1-x Al x The N layer is a sublayer that is part of a multilayer of at least Ti 1-y Al y N and Ti 1-z Al z A multilayer of alternating sublayers of N, wherein 0.40≤y≤0.65 and 0.80≤z≤0.98, only a cubic phase exists, and the average thickness of each (Ti,Al)N sublayer is 1 nm to 20 nm.

3. The method according to any one of claims 1 to 2, wherein the Ti 1-x Al x The N layer is deposited under a vacuum chamber pressure of 10Pa to 12Pa of N2 gas.

4. The method according to any one of claims 1 to 2, wherein the Ti 1-x Al x The N layer is deposited using a DC bias voltage of -250V to -350V.

5. A coated cutting tool for metal processing manufactured according to the method of claim 2, the coated cutting tool having a coating comprising at least Ti 1-y Al y N and Ti 1-z Al z The (Ti,Al)N multilayer has alternating sublayers of N, wherein 0.40≤y≤0.65 and 0.80≤z≤0.98, and only a cubic phase exists in the form of a single-phase cubic structure, and the average thickness of a single (Ti,Al)N sublayer is 1nm to 20nm, and the (Ti,Al)N multilayer is a non-periodic multilayer.

6. The coated cutting tool according to claim 5, wherein 0.40≤y≤0.6 and 0.85≤z≤0.

96.

7. The coated cutting tool according to any one of claims 5-6, wherein the average thickness of the single sub-layer is from 1.5 nm to 5 nm.

8. The coated cutting tool according to any one of claims 5-6, wherein the total thickness of the (Ti,Al)N multilayer is 0.5 μm to 10 μm.

9. The coated cutting tool according to any one of claims 5-6, wherein the (Ti,Al)N multilayer is a cathodic arc evaporation deposited multilayer.

10. The coated cutting tool according to any one of claims 5-6, wherein the substrate of the coated cutting tool is selected from cemented carbide, ceramic and high speed steel.

11. The coated cutting tool according to any one of claims 5-6, wherein the substrate of the coated cutting tool is selected from the group consisting of cermet and cubic boron nitride.

12. The coated cutting tool according to any one of claims 5-6, wherein the coated cutting tool is a cutting tool insert, a drill or a solid end mill for metal machining.

Citation Information

Patent Citations

  • Al-rich aitin-based films

    WO2019048507A1

  • Multilayered coated cutting tool

    CN101952482A

  • Coated cutting tool

    EP3441168A1